Etika Bisnis dan Good Corporate Governance pada PT Unilever Indonesia Tbk di Era ESG - Nina Hartati; Steffany Rusli; Tasya; Fabiola; Cathabella Gilliani; Susan Grace V Nainggolan (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the implementation of business ethics and Good Corporate Governance (GCG) principles at PT Unilever Indonesia Tbk (Unilever Indonesia), evaluating their impact on reporting transparency, company performance, and stakeholder trust. The research method used is a qualitative descriptive case study based on documents (Annual Report, Sustainability Report, governance policies) enriched through triangulation with media coverage related to reputation issues for the 2024–2025 period. The results show that Unilever Indonesia has an established governance systems and code of ethics, as well as comprehensive ESG reporting practices, but faces reputational and market pressures (including the impact of geopolitical issues and adjustments to global sustainability targets) that challenge the implementation of ethics and public perception of ESG commitments. The study discusses academic and practical implications, and recommends steps to improve communication governance and strengthen operational integrity.